STUDENTS’ DIFFICULTIES IN FINISHING A THESIS OF ENGLISH STUDY PROGRAM AT MUHAMMADIYAH UNIVERSITY OF TANGERANG - Abdul Rohim (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
This study aims to determine the difficulties faced by students of Muhammadiyah University of Tangerang   English   Education   Study   Program in conducting research and writing a thesis as their final project in the University.  This  type  of  research  is  descriptive  research.  The subjects  of  this  study  were  undergraduate  students  of  the  English education study program who were undergraduate thesis guidance in 2020.   Data   collection   in   this   study   used   questionnaires .  The  questionnaire  is  given  to  students  who  are  writing their  thesis.  Data  were  analyzed  using  percentage  techniques  which were  further  described.  The  results  of  the  study  generally  show  that there are various factors of difficulties faced by students in conducting research   and writing it into thesis, both psychological factors and sociocultural factors.  Psychological factors are  caused  by challenges of adapting research topics to the current situation, lack  of  understanding  of  research  methods  and  academic writing   styles and  lack of motivation..   In   sociocultural factors,   student   difficulties   are dominated by social factors from their friends, parents and supervisors.